TINJAUAN TENTANG PENOLAKAN PEMERINTAH REPUBLIK INDONESIA ATAS KEPULANGAN WARGA NEGARA INDONESIA EKS ISIS (ISLAMIC STATE OF IRAQ AND SYRIA) DITINJAU DARI HUKUM POSITIF INDONESIA - Keivelyn Lovelycia; Tatang Ruchimat (Jurnal Hukum Adigama, 2020)
The discourse of returning Indonesian citizens ex-ISIS (Islamic State of Iraq and Syria) to Indonesia in February 2020 has generated a lot of debate in the community. On Wednesday, February 12 2020, President Joko Widodo has decided not to allow 689 ex-ISIS Indonesians to return to their homeland for safety reasons. This decision is deemed contrary to positive Indonesian law, where Indonesian citizens may not be prohibited from entering / returning to Indonesia. Then what is the state's responsibility towards ex-ISIS citizens when viewed from Indonesia's positive law? In this research, normative legal research methods will be used. The research results show that ex-ISIS Indonesian citizens should not be prohibited from returning to Indonesia because they still have Indonesian citizenship status and ex-ISIS citizens can be subject to Indonesian criminal penalties and must carry out deradicalization as regulated in Indonesian legislation. The Indonesian government should reconsider the return of ex-ISIS citizens to Indonesia as regulated in Indonesia's positive law. If the Indonesian Government continues to take steps to refuse their return, then it is better if the government provides a strong legal basis and reasons for refusing their return.